Electrolyte additive, electrolyte and battery

By adding silicon-based fluorophosphate and isocyanate compounds to the electrolyte of lithium-ion batteries, a stable interface film is formed, which solves the performance stability of lithium-ion batteries under high voltage and high temperature conditions, and achieves excellent cycle stability and high temperature storage performance.

CN119674234AActive Publication Date: 2025-03-21JIUJIANG TINCI ADVANCED MATERIALS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411741777.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Lithium-ion batteries have poor performance stability under high voltage and high temperature conditions, and the electrolyte is prone to side reactions with the electrode material, resulting in unstable interface, increasing the internal resistance of the battery, and reducing its cycling stability and safety.

Method used

An electrolyte additive is adopted, which includes silicon-based fluorophosphate compounds and isocyanate compounds, which can form a stable interface film on the surface of the electrode sheet, and has the characteristics of strong stability, smooth and flatness, uniform thickness, good flexibility, high conductivity and corrosion resistance.

Benefits of technology

Under high voltage conditions, the battery has excellent cycle stability and high temperature storage performance, which reduces the internal resistance of the battery and improves its cycle life and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674234A_ABST
    Figure CN119674234A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte additive, an electrolyte and a battery. The electrolyte additive comprises a first additive and a second additive, the first additive comprises a compound shown as a formula I: # imgabs0 # R1, R2 and R3 independently comprise any one of H, F, C1-C4 alkyl groups, C1-C4 fluoroalkyl groups, C2-C4 alkenyl groups, C2-C4 fluoroalkenyl groups, C2-C4 alkynyl groups, C5-C7 cycloalkane, R4 substituted phenyl groups and R5 substituted benzyl groups, and R1, R2 and R3 independently comprise any one of H, F, C1-C4 alkyl groups, C1-C4 fluoroalkyl groups, C2-C4 alkenyl groups, C2-C4 fluoroalkenyl groups, C2-C4 alkynyl groups, C5-C7 cycloalkane, R4 substituted phenyl groups and R5 substituted benzyl groups; r4 and R5 are respectively and independently selected from any one of H, alkyl of C1-C4, alkenyl of C2-C4, alkynyl of C2-C4, fluoroalkyl of C1-C4, fluoroalkenyl of C2-C4 and fluoroalkynyl of C2-C4; the second additive comprises an isocyanate compound. An interfacial film formed on the surface of a pole piece by the electrolyte additive is high in stability, smooth and flat, uniform in thickness, good in flexibility, high in conductivity and resistant to corrosion, so that the battery has excellent cycling stability and high-temperature storage performance under a high-voltage condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of material preparation, and in particular, to an electrolyte additive, an electrolyte and a battery. Background Art

[0002] With the development of energy storage technology, secondary batteries, especially lithium-ion batteries, have become the preferred power source for portable electronic devices, electric vehicles and large-scale energy storage systems due to their high energy density, long cycle life and environmental friendliness. However, the performance stability of lithium-ion batteries under high voltage and high temperature conditions remains a technical challenge. The electrolyte of the battery is prone to side reactions with the electrode material, resulting in unstable interfaces, increasing the internal resistance of the battery, and reducing its cycle stability and safety. Summary of the invention

[0003] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes an electrolyte additive, an electrolyte and a battery, wherein the electrolyte additive forms an interface film on the surface of the pole piece that is stable, smooth, uniform in thickness, flexible, highly conductive and corrosion-resistant, so that the battery has excellent cycle stability and high-temperature storage performance under high voltage conditions.

[0004] In a first aspect, the present application provides an electrolyte additive, the electrolyte additive comprising a first additive and a second additive;

[0005] The first additive includes a compound shown in Formula I:

[0006] R1, R2 and R3 each independently include any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkane, R4 substituted phenyl and R5 substituted benzyl;

[0007] R4 and R5 are each independently selected from any one of H, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl and C2-C4 fluoroalkynyl;

[0008] The second additive includes an isocyanate compound.

[0009] The electrolyte additive of the present application has excellent film-forming properties. The interface film formed on the surface of the electrode is stable, smooth, uniform, flexible, highly conductive and corrosion-resistant, so that the battery has excellent cycle stability and high-temperature storage performance under high voltage conditions.

[0010] According to an embodiment of the present application, the first additive includes at least one of the compounds having structures shown in Formulae 1-1 to 1-22:

[0011]

[0012]

[0013] According to an embodiment of the present application, the isocyanate compound includes at least one of hexamethylene diisocyanate, p-phenylene diisocyanate, toluene-2,4-diisocyanate and 4,4-diisocyanate dicyclohexylmethane.

[0014] According to an embodiment of the present application, the mass ratio of the first additive to the second additive is (0.06-50):1.

[0015] The second aspect of the present application provides an electrolyte, which includes: the electrolyte additive described in the first aspect.

[0016] According to an embodiment of the present application, the added amount of the first additive accounts for 0.05% to 5% of the total mass of the electrolyte.

[0017] According to an embodiment of the present application, the added amount of the second additive accounts for 0.03% to 1% of the total mass of the electrolyte.

[0018] According to an embodiment of the present invention, the electrolyte further comprises lithium salt, and the amount of the lithium salt added accounts for 8% to 20% of the total mass of the electrolyte.

[0019] According to an embodiment of the present invention, the lithium salt includes at least one of LiPF6, LiAsF6, LiClO4, LiSO3CF3, LiBF4, LiB(C2O4)2, LiBF2C2O4, LiN(SO2F)2, LiN(SO2CF3)2, LiPO2F2, LiPF2(C2O4)2 and LiPF4C2O4.

[0020] According to an embodiment of the present invention, the lithium salt further includes a non-aqueous organic solvent; the added amount of the non-aqueous organic solvent accounts for 70% to 92% of the total mass of the electrolyte.

[0021] According to an embodiment of the present invention, the non-aqueous organic solvent includes at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, cyclopentane, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl acetate, propyl propionate, ethyl propionate, propyl acetate, methyl propionate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2-difluoroethyl acetate, and methyl-(2,2,2-trifluoroethyl) carbonate.

[0022] The third aspect of the present application provides a battery, comprising: the electrolyte additive described in the first aspect or the electrolyte described in the second aspect.

[0023] According to an embodiment of the present application, the battery further comprises: a positive electrode sheet, a negative electrode sheet and a separator; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side surface of the positive electrode current collector, and the positive electrode active material layer comprises a positive electrode active material;

[0024] The positive electrode active material includes LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, LiNi x Co y Mn z M 1-x-y-z O2、Li 1+a Mn 1-x M x O2、LiCo 1-x M x O2、LiFe 1-x M x PO4、Li2Mn 1-x O4、Na m At least one of AO2, polyanionic compounds, and Prussian blue compounds; wherein M is selected from at least one of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B and F, A includes at least one of Ti, V, Mn, Co, Ni, Fe, Zn, V, Zr, Ce, Cr, and Cu, 0≤a<0.2, 0≤x<1, and 0<m≤1.

[0025] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0026] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0027] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0028] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers, and the scope limited in this way can be including end values ​​a and b. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0029] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0030] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0031] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0032] In a first aspect, the present application provides an electrolyte additive, the electrolyte additive comprising a first additive and a second additive;

[0033] The first additive includes a compound shown in Formula I:

[0034] R1, R2 and R3 each independently include any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkane, R4 substituted phenyl and R5 substituted benzyl;

[0035] R4 and R5 are each independently selected from any one of H, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl and C2-C4 fluoroalkynyl;

[0036] The second additive includes an isocyanate compound.

[0037] The electrolyte additive of the present application has excellent film-forming properties. The interface film formed on the surface of the electrode is stable, smooth, uniform, flexible, highly conductive and corrosion-resistant, thereby enabling the battery to have excellent cycle stability and high-temperature storage performance under high voltage conditions.

[0038] The following is a detailed description of the principle by which the present application can achieve the above beneficial effects:

[0039] The silicon-based fluorophosphate compound (first additive) in the electrolyte additive of the present application can form a stable CEI (positive electrode electrolyte interface) film and SEI (negative electrode electrolyte interface) film on the surface of the positive electrode plate and the negative electrode plate, effectively preventing the interface side reaction between the electrode material and the electrolyte, and having strong corrosion resistance, thereby protecting the electrode material and the electrolyte. At the same time, it helps to optimize the transmission of ions, reduce the interface impedance, and improve the conductivity, which has a significant improvement effect on the cycle stability and high temperature performance of the battery. In addition, the organic group in the silicon-based fluorophosphate compound provides good flexibility, so that the interface film can adapt to the deformation of the electrode material when the volume expands and contracts during the battery charging and discharging process, reduce the generation of cracks, and maintain the integrity of the film.

[0040] However, the lithium salt LiPF6 in the electrolyte can be decomposed into phosphorus pentafluoride, and phosphorus pentafluoride undergoes the following reaction PF5+H2O→POF3+HF. The HF in the electrolyte will react with silicon-based fluorophosphate to produce fluorosilane-like gas, causing the battery to produce serious gas production and diving after a period of storage or circulation. Therefore, the second additive-isocyanate compound is introduced. The isocyanate functional group is an electron donor, which can attract phosphorus pentafluoride to form a complex, thereby stabilizing and inactivating phosphorus pentafluoride, reducing the generation of HF, and effectively reducing the generation of fluorosilane-like gas in silicon-based fluorophosphate compounds during storage or circulation. However, the isocyanate compound itself will reduce and polymerize to form an amide compound, which will reduce the ion transfer rate while improving the stability of the SEI film. The first additive has a higher reactivity and can be reduced before the isocyanate additive to form lithium fluoride, lithium phosphate and Li x PO y F z etc. to improve the SEI membrane components that can transport ions, thereby reducing the negative effects of isocyanates.

[0041] In summary, silicon-based fluorophosphate compounds and isocyanate compounds complement each other and jointly promote the formation of a uniform and stable interface film while maintaining a low interface impedance, thereby enabling the battery to have excellent cycle stability and storage performance under high voltage and high temperature conditions.

[0042] According to an embodiment of the present application, the first additive includes at least one of the compounds having structures shown in Formulae 1-1 to 1-22:

[0043]

[0044]

[0045] Among them, the CAS numbers of formulas 1-1 to 1-17 are:

[0046] 1-1: 2708941-25-5; 1-2: 4419-25-9; 1-3: 13683-39-1; 1-4: 4414-27-1; 1-5: 4414-26-0; 1-6: 4480-02-8; 1-7: 2577172-95-1; 1-8: 13683-40-4; 1-9: 2577172-93 -9; 1-10: 2708941-27-7; 1-11: 2287283-36-5; 1-12: 6231-57-8; 1-13: 1386-54-9; 1-14: 2708941-26-6; 1-15: 6231-58-9; 1-16: 6231-59-0; 1-17: 2577172-94-0

[0047] The synthesis method of 1-18 to 1-22 is prepared by referring to the preparation method of Example 14 in patent CN114728992A. Specifically, the raw materials shown below are used to replace the chlorodimethylphenylsilane in the reference document.

[0048] The raw material is trivinyl chlorosilane (1871-21-2)

[0049] The raw material is dimethyl butyl chlorosilane (2069196-19-4)

[0050] The raw material is dimethyl (trifluoropropylene) chlorosilane (89705-02-2)

[0051] The raw material is tris(pentafluoroethyl)chlorosilane (1620665-21-5)

[0052] The raw material is dimethyl (p-methylbenzyl) chlorosilane (1833-28-9)

[0053] The first additive has good film-forming properties and can form an interface film with good stability, corrosion resistance and flexibility on the surface of the pole piece, which protects the electrode material and the electrolyte. At the same time, the ion transmission rate is high, the interface impedance is low, and the conductivity is high, which can better offset the negative effects of isocyanate compounds, thereby further improving the stability of the battery under high temperature and high pressure conditions.

[0054] According to an embodiment of the present application, the isocyanate compound includes at least one of hexamethylene diisocyanate, p-phenylene diisocyanate, toluene-2,4-diisocyanate and 4,4-diisocyanate dicyclohexylmethane. The above isocyanate compounds can further improve the situation of excessive acidity and severe battery gas production caused by silicon-based fluorophosphate compounds under high voltage and high temperature conditions, thereby further improving the stability of the battery under high temperature and high pressure conditions.

[0055] According to an embodiment of the present application, the mass ratio of the first additive to the second additive is (0.06-50):1, for example, it can be 0.06:1, 0.1:1, 0.5:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 20:1, 50:1. The first additive and the second additive meet the above conditions, and an interface film with good stability, corrosion resistance and flexibility can be formed on the surface of the pole piece, while the ion transfer rate is high, the interface impedance is low, and the conductivity is high. In addition, it can further improve the situation of excessive acidity and severe battery gas production caused by silicon-based fluorophosphate compounds under high voltage and high temperature conditions, thereby further improving the stability of the battery under high temperature and high pressure conditions.

[0056] The second aspect of the present application provides an electrolyte, the electrolyte comprising: the electrolyte additive described in the first aspect. Thus, the electrolyte has all the characteristics and advantages of the aforementioned electrolyte additive, which will not be repeated here. In general, the interface film formed at least on the surface of the pole piece has strong stability, smoothness, uniform thickness, good flexibility, high conductivity and corrosion resistance, thereby enabling the battery to have excellent cycle stability and high temperature storage performance under high voltage conditions.

[0057] According to some embodiments of the present application, the amount of the first additive added is 0.05% to 5% of the total mass of the electrolyte, for example, it can be 0.05%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%. The amount of the first additive added meets the above conditions and can have better film-forming properties, and can form an interface film with good stability, corrosion resistance and flexibility on the surface of the pole piece, which plays a protective role on the electrode material and the electrolyte. At the same time, the ion transfer rate is high, the interface impedance is low, and the conductivity is high, which can better offset the negative effects of isocyanate compounds, thereby further improving the stability of the battery under high temperature and high pressure conditions.

[0058] According to some embodiments of the present application, the amount of the second additive added is 0.03% to 1% of the total mass of the electrolyte, for example, 0.05%, 0.1%, 0.5%, or 1.0%. The amount of the second additive added satisfies the above conditions, which can further improve the situation of excessive acidity and severe gas production of the battery caused by the silicon-based fluorophosphate compound under high voltage and high temperature conditions, thereby further improving the stability of the battery under high temperature and high pressure conditions.

[0059] According to some embodiments of the present application, the electrolyte further includes: lithium salt, the amount of lithium salt added accounts for 8% to 20% of the total mass of the electrolyte, for example, it can be 8%, 10%, 12%, 15%, 18%, 20%. As a result, the lithium salt meets the above conditions, and the efficient migration and stable transmission of ions in the electrolyte improve the charging and discharging efficiency and power density of the battery. In addition, it helps to maintain the chemical stability of the electrolyte and reduce side reactions during high-voltage charging, such as decomposition of the electrolyte and generation of gas, which helps to extend the cycle life of the battery and improve its safety.

[0060] As an example, the lithium salt includes at least one of LiPF6, LiAsF6, LiClO4, LiSO3CF3, LiBF4, LiB(C2O4)2, LiBF2C2O4, LiN(SO2F)2, LiN(SO2CF3)2, LiPO2F2, LiPF2(C2O4)2 and LiPF4C2O4.

[0061] According to some embodiments of the present application, the electrolyte further includes: a non-aqueous organic solvent, the addition amount of the non-aqueous organic solvent accounts for 70% to 92% of the total mass of the electrolyte, for example, it can be 70%, 72%, 75%, 78%, 80%, 82%, 85%, 87%, 90%, 92%. The non-aqueous organic solvent meets the above conditions and can enable ions to migrate efficiently and be evenly distributed in the electrolyte, thereby improving the charge and discharge efficiency and cycle stability of the battery. In addition, it helps to form a stable SEI film, reduce the decomposition of the electrolyte and the dissolution of transition metals, and extend the service life of the battery. At the same time, it can also optimize the thermal stability and safety of the battery, reduce the risk of side reactions and overheating under high temperature conditions, and enable the battery to maintain excellent performance under various operating conditions.

[0062] As an example, the non-aqueous organic solvent includes at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, cyclopentane, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methylpropyl carbonate, ethyl acetate, propyl propionate, ethyl propionate, propyl acetate, methyl propionate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2-difluoroethyl acetate, and methyl-(2,2,2-trifluoroethyl) carbonate.

[0063] The third aspect of the present application provides a battery, the battery comprising: the electrolyte additive described in the first aspect or the electrolyte described in the second aspect. As a result, the battery has all the characteristics and advantages of the aforementioned electrolyte, which will not be repeated here. In general, at least the battery has internal resistance, the battery is not easy to produce gas, and has excellent cycle stability and high temperature storage performance under high voltage conditions.

[0064] According to some embodiments of the present application, the battery further includes: a positive electrode sheet, a negative electrode sheet and a separator. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays a role in conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly playing a role in preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0065] According to some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material; the positive electrode active material includes LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, LiNi x Co y Mn z M 1-x-y-z O2、Li 1+a Mn 1-x M x O2、LiCo 1-x M x O2、LiFe 1-x M x PO4、Li2Mn 1-x O4、Na m At least one of AO2, polyanionic compounds, and Prussian blue compounds; wherein M is selected from at least one of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B, and F, and A includes at least one of Ti, V, Mn, Co, Ni, Fe, Zn, V, Zr, Ce, Cr, and Cu, 0≤a<0.2, 0≤x<1, and 0<m≤1.

[0066] According to some embodiments of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the surface of the polymer material base. For example, the composite positive electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).

[0067] According to some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0068] According to some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0069] According to some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0070] According to some embodiments of the present application, the negative electrode sheet includes a negative electrode active material layer, and the negative electrode active material layer includes a binder.

[0071] According to some embodiments of the present application, the binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0072] According to some embodiments of the present application, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: soft carbon, hard carbon, silicon-based material, tin-based material, etc., and the soft carbon includes graphite. The silicon-based material may include at least one of elemental silicon, silicon oxide compound, silicon carbon composite, silicon nitrogen composite and silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide compound and tin alloy.

[0073] According to some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0074] According to some embodiments of the present application, the negative electrode active material layer may further optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0075] According to some embodiments of the present application, the negative electrode plate includes a negative electrode current collector, and the negative electrode active material layer is disposed on at least one side surface of the negative electrode current collector.

[0076] According to some embodiments of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, aluminum or copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (aluminum, copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).

[0077] According to some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0078] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.

[0079] According to some embodiments of the present application, the material of the isolation membrane may include one or more of polyolefin, aromatic polyamide, polytetrafluoroethylene, and polyethersulfone. Further, the isolation membrane includes one or both of polyethylene and polypropylene. In addition, the diaphragm may be obtained by stacking multiple layers of materials in sequence, for example, the isolation membrane includes a polypropylene layer, a polyethylene layer, and a polypropylene layer stacked in sequence.

[0080] According to some embodiments of the present application, the thickness of the isolation film may be 9 μm-12 μm, for example, 9 μm, 10 μm, 11 μm, 12 μm, etc.

[0081] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0082] Example 1

[0083] 1. Preparation of electrolyte: The electrolyte of this embodiment is prepared with the following components according to mass fraction: 12.5% ​​LiPF6,

[0084] 1.0% of the compound of formula 1, 0.3% of hexamethylene diisocyanate, and a non-aqueous organic solvent (the mass ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) is 3:5:2) to make up to 100%.

[0085] 2. Positive electrode preparation: LiNi 0.6 Co 0.2 Mn 0.2 O2 positive electrode material (NCM523), conductive agent SuperP (conductive carbon black), conductive agent CNT (carbon nanotube), adhesive PVDF (polyvinylidene fluoride) were mixed evenly in a mass ratio of 96.3:2:0.5:1.2, vacuum stirred until the fluidity was uniform, and then the slurry was evenly coated on the front and back of the aluminum foil, and then dried at 85°C, cold pressed, trimmed, cut, stripped, and vacuum dried at 85°C for 12 hours. After welding the pole ears, the surface density was 33 mg / cm 2 The positive electrode.

[0086] 3. Negative electrode preparation: Graphite negative electrode material, conductive agent Super P (conductive carbon black), thickener CMC (sodium carboxymethyl cellulose), and adhesive SBR (styrene-butadiene rubber latex) are fully mixed into a uniform slurry at a mass ratio of 96:1.5:1.5:2. After coating on both sides of the copper foil, it is dried at 85°C, and then cold pressed, trimmed, cut into pieces, and striped. Finally, it is dried under vacuum conditions at 85°C for 12 hours. The electrode ear is welded to obtain a surface density of 19.3 mg / cm 2 The negative electrode.

[0087] 4. Diaphragm: A 9 μm thick polyethylene porous polymer film is used as the substrate, and a 2 μm adhesive coating is coated on both sides of the substrate.

[0088] 5. Lithium-ion battery preparation:

[0089] The positive electrode sheet, separator and negative electrode sheet are stacked in sequence and wound into a bare cell with a theoretical capacity of 1600 mAh. The bare cell is placed in an outer packaging aluminum foil and vacuum-baked at 75°C for 10 hours before injecting the electrolyte. After vacuum packaging, standing, formation, aging, capacity division and other processes, the lithium-ion battery is completed.

[0090] The preparation methods of Examples 1 to 42 and Comparative Examples 1 to 9 are the same as those of Example 1, and the differences are detailed in Table 1.

[0091] Test Case

[0092] The lithium-ion batteries prepared in Examples 1 to 42 and Comparative Examples 1 to 9 were respectively tested for impedance, cycle and high and low temperature performance. The testing method for the NCM523 battery is as follows: the difference between the testing method for the lithium cobalt oxide (LiCoO2) battery and the NCM523 battery is that the charging cut-off voltage is 4.48V and the discharging cut-off voltage is 3.0V; the difference between the testing method for the lithium iron phosphate (LiFePO4) battery and the NCM523 battery is that the charging cut-off voltage is 3.65V and the discharging cut-off voltage is 2.0V.

[0093] 25℃ normal temperature cycle test: Charge to 4.4V at 1.0C constant current at 25℃, charge to cut-off current 0.05C at 4.4V constant voltage, then discharge to 2.75V at 1.0C constant current. Repeat the charge and discharge steps for 1000 cycles. Record the discharge capacity of the 1000th cycle and the 1st cycle and divide them to get the capacity retention rate.

[0094] 45℃ high temperature cycle test: Charge to 4.4V at 1.0C constant current at 45℃, charge to 0.05C at 4.4V constant voltage, then discharge to 2.75V at 1.0C constant current. Repeat the charge and discharge steps for 800 cycles. Record the discharge capacity of the 800th cycle and the first cycle, and divide the two to get the capacity retention rate.

[0095] 60℃ high temperature 30-day storage test: At 25℃, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, and then discharge the battery to 2.75V at 1.0C constant current. The discharge capacity is recorded as C1. At 25℃, charge to 4.4V at 1.0C constant current, charge to 0.05C at 4.4V constant voltage, and then transfer the battery to 60℃ for 30 days. Then discharge the battery to 2.75V at 1.0C constant current. The discharge capacity is recorded as C2. The capacity retention rate of 30-day storage at 60℃ = C2 / C1*100%.

[0096] Initial DCIR test: Charge the lithium-ion battery at 25°C at a constant current of 1.0C to 4.4V, charge at a constant voltage of 4.4V to a cut-off current of 0.05C, then discharge the battery at a constant current of 1.0C for 30min. After standing for 1h, discharge it at a constant current of 2.0C for 10s, and calculate the DCIR impedance value of the battery at 50% SOC.

[0097] The results are shown in Table 1.

[0098]

[0099]

[0100]

[0101]

[0102]

[0103]

[0104]

[0105] It can be seen that the overall performance of the lithium ion batteries prepared in Examples 1 to 42 is better than that of the lithium ion batteries prepared in Comparative Examples 1 to 5. The present application can significantly improve the normal temperature cycle, high temperature cycle stability and storage performance of the battery by compounding the first additive and the second additive and adding them to the lithium ion battery, and can well reduce the initial DCR value.

[0106] It can be seen from Comparative Examples 1, 3, 6, and 8 that if isocyanate compounds are not added, silicon-based fluorophosphate compounds are likely to cause abnormal changes in electrolyte acidity, the thickness of the formed interface film is uneven, abnormal gas is likely to be generated, the surface of the electrode material is relatively rough and the interface impedance is large, resulting in poor battery cycle performance and high-temperature storage performance under high voltage and room temperature and high temperature conditions. Examples 1, 39, and 40 can effectively improve the situation of excessive acidity and severe battery gas production caused by silicon-based fluorophosphate compounds under high voltage and high temperature conditions by adding isocyanate compounds, thereby improving the battery cycle performance and high-temperature storage performance under high voltage and room temperature and high temperature conditions.

[0107] It can be seen from Comparative Examples 2, 4, 7, and 9 that if the silicon-based fluorophosphate compound is not added, the isocyanate compound will reduce the lithium ion transmission rate, resulting in a higher battery impedance and a poor cycle life. Examples 1, 39, and 40 can effectively improve lithium ion transmission and offset the negative effects of the isocyanate compound by adding a silicon-based fluorophosphate compound, which is manifested in improving the battery's cycle performance and high-temperature storage performance under high temperature and high voltage conditions.

[0108] It can be seen from Comparative Example 5 that although the addition of tri(trimethylsilyl)phosphine can slightly improve the cycle and storage performance of the battery, the magnitude is far less than that of the compound of formula I, and tri(trimethylsilyl)phosphine fails to reduce the initial impedance value of the battery.

[0109] It can be seen from Example 2, Example 32 and Example 33 that the content of the first additive is too little, and the degree of improvement is very limited; the content of the first additive is too much, resulting in the formation of an SEI film that is too thick, which cannot reduce the DCR and improve the cycle.

[0110] It can be seen from Example 2, Example 34 and Example 35 that if the content of the second additive is too little, the water removal and acid inhibition effect of the second additive is difficult to exert, resulting in no obvious performance improvement; if the content of the second additive is too much, the impedance will increase rapidly, reducing the transmission efficiency of lithium ions, which is manifested as a significant increase in impedance.

[0111] It can be seen from Examples 26-38 that the mass ratio of the first additive to the second additive is too small, and the silicon-based fluorophosphate additive is difficult to offset the negative impact of the isocyanate additive, resulting in still large impedance and poor cycle life; the mass ratio of the first additive to the second additive is too large, and the isocyanate additive is difficult to eliminate the problem of easy hydrolysis and gas production of the silicon-based fluorophosphate additive, resulting in an unsatisfactory cycle life.

[0112] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. An electrolyte additive, characterized in that: including a first additive and a second additive; The first additive includes a compound shown in Formula I: R1, R2 and R3 each independently include any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkane, R4 substituted phenyl and R5 substituted benzyl; R4 and R5 are each independently selected from any one of H, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, C2-C4 fluoroalkenyl and C2-C4 fluoroalkynyl; The second additive includes an isocyanate compound.

2. The electrolyte additive according to claim 1, characterized in that: The first additive includes at least one of the compounds having structures shown in Formulas 1-1 to 1-22:

3. The electrolyte additive according to claim 1 or 2, characterized in that: The isocyanate compound includes at least one of hexamethylene diisocyanate, p-phenylene diisocyanate, toluene-2,4-diisocyanate and 4,4-diisocyanate dicyclohexylmethane.

4. The electrolyte additive according to any one of claims 1 to 3, characterized in that: The mass ratio of the first additive to the second additive is (0.06-50):

1.

5. An electrolyte, characterized in that: include: The electrolyte additive according to any one of claims 1 to 4.

6. The electrolyte according to claim 5, characterized in that The added amount of the first additive accounts for 0.05% to 5% of the total mass of the electrolyte.

7. The electrolyte according to claim 5, characterized in that The added amount of the second additive accounts for 0.03% to 1% of the total mass of the electrolyte.

8. The electrolyte according to claim 5, characterized in that It further comprises lithium salt, and the addition amount of the lithium salt accounts for 8% to 20% of the total mass of the electrolyte.

9. The electrolyte according to claim 8, characterized in that The lithium salt includes at least one of LiPF6, LiAsF6, LiClO4, LiSO3CF3, LiBF4, LiB(C2O4)2, LiBF2C2O4, LiN(SO2F)2, LiN(SO2CF3)2, LiPO2F2, LiPF2(C2O4)2 and LiPF4C2O4.

10. The electrolyte according to claim 5, characterized in that It further comprises a non-aqueous organic solvent; the addition amount of the non-aqueous organic solvent accounts for 70% to 92% of the total mass of the electrolyte.

11. The electrolyte according to claim 10, characterized in that The non-aqueous organic solvent includes at least one of ethylene carbonate, propylene carbonate, γ-butyrolactone, cyclopentane, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methyl propyl carbonate, ethyl acetate, propyl propionate, ethyl propionate, propyl acetate, methyl propionate, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 2,2-difluoroethyl acetate, and methyl-(2,2,2-trifluoroethyl) carbonate.

12. A battery, characterized in that: The invention comprises the electrolyte additive according to any one of claims 1 to 4 or the electrolyte according to any one of claims 5 to 11.

13. The battery according to claim 12, characterized in that Further including: A positive electrode sheet, a negative electrode sheet and a separator; the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer comprising a positive electrode active material; The positive electrode active material includes LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, LiNi x Co y Mn z M 1-x-y- z O2、Li 1+a Mn 1-x M x O2、LiCo 1-x M x O2、LiFe 1-x M x PO4、Li2Mn 1-x O4、Na m At least one of AO2, polyanionic compounds, and Prussian blue compounds; wherein M is selected from at least one of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B and F, A includes at least one of Ti, V, Mn, Co, Ni, Fe, Zn, V, Zr, Ce, Cr, and Cu, 0≤a<0.2, 0≤x<1, and 0<m≤1.

Citation Information

Patent Citations

  • Nonaqueous-electrolyte battery

    CN104953174A

  • Electrolyte additive for lithium secondary battery, electrolyte for lithium secondary battery comprising same, and lithium secondary battery

    CN114402468A

  • Method for producing phosphate compound

    CN114728992A

  • Electrolyte, secondary battery, and electric device

    CN115149102A

  • Synthesis method of estersil compound containing difluorophosphoric acid or phosphorous acid group

    CN116496315A